The Relationship Between Digital-Based Learning Management and The Quality of Education - Asep Encu; Dicky Juliansyah (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
The use of technology in education field, especially in student learning activity, began to be widely used after the Covid-19 pandemic. However, the use of technology in student learning often causes problems that can hinder the learning process. These problems include a poor internet network, limited digital learning facilities and inadequate teacher skills in using technology. Therefore, the importance of providing adequate facilities and training for educators is a priority to be realized. This research was carried out with the aim of finding out the relationship between digital-based learning management and the quality of education at MAN Bandung Regency. This research uses a quantitative approach with a correlational descriptive method. Research findings show that the correlation test results are 0.000